The 'Civic-minded' Professional? An exploration through Hannah Arendt's 'vita activa'. Issue 2 (28th January 2016) - Kreber, Carolin
Abstract: Recent reform initiatives calling for 'civic' ('public-good' or 'democratic') professionalism can be seen as a response to the widely reported decline in public trust in the professions and an attempt to partially remedy this problem through a more publically engaged professionalism. The author draws on the political philosophy of Hannah Arendt, identifying the strong, albeit in the professionalism literature rarely acknowledged, affinities between civic professionalism and her concept of action as (collective) freedom through public deliberation. Using the three modalities of the active life that Arendt discusses in The Human Condition (labour, work and action) as analytical tools, the author suggests that changing conditions in the public sector have led to professional life increasingly taking on the forms of labour and work, at the expense of action. The implications of these developments are highlighted before the author proceeds to show that a professional life oriented strongly towards action is consistent with 'civic' professionalism based on community engagement. Some of the main approaches traditionally taken to promote a civic orientation among university students are noted; the article concludes with a discussion of how the specific concepts underlying Arendtian action can be put to work in university pedagogies to intentionally promote the public 'civic-minded professional'.